2019
DOI: 10.1186/s13073-019-0684-0
|View full text |Cite
|
Sign up to set email alerts
|

Neoantigens and genome instability: impact on immunogenomic phenotypes and immunotherapy response

Abstract: The resurgence of immune therapies in cancer medicine has elicited a corresponding interest in understanding the basis of patient response or resistance to these treatments. One aspect of patient response clearly lies in the genomic alterations that are associated with cancer onset and progression, including those that contribute to genomic instability and the resulting creation of novel peptide sequences that may present as neoantigens. The immune reaction to these unique ‘non-self’ peptides is frequently sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 94 publications
4
57
0
Order By: Relevance
“…The results showed that, especially CD16+ and CD68+ cells, were associated with an affirmative response to ICIs, as well as prolonged survival. Subsequent studies including patients with NSCLC or metastatic melanoma receiving ICIs discovered that neoantigens coded by DNA with loss-of-function mutations can result in drug resistance ( 138 140 ). Alterations in PD-L1 and PD-L2 copy number ( 141 ), as well as microsatellite instability/mismatch-repair deficiency ( 142 ) were identified as potential predictive biomarkers.…”
Section: Predictive Indicators For Combination Therapy Of Anti-angiogmentioning
confidence: 99%
“…The results showed that, especially CD16+ and CD68+ cells, were associated with an affirmative response to ICIs, as well as prolonged survival. Subsequent studies including patients with NSCLC or metastatic melanoma receiving ICIs discovered that neoantigens coded by DNA with loss-of-function mutations can result in drug resistance ( 138 140 ). Alterations in PD-L1 and PD-L2 copy number ( 141 ), as well as microsatellite instability/mismatch-repair deficiency ( 142 ) were identified as potential predictive biomarkers.…”
Section: Predictive Indicators For Combination Therapy Of Anti-angiogmentioning
confidence: 99%
“…Various forms of genomic instability in cancers produce new antigens and immune-responsive phenotypes eventually [14]. In the analysis of LCCs and RCCs, we have con rmed that genomic instability does affect the immune response and the prognosis through a series of potential mechanisms.…”
Section: Discussionmentioning
confidence: 85%
“…Also, a variety of biological processes are related to genome instability, including abnormal transcription and post-transcriptional regulation, DNA damage regulation, etc [13]. Latest ndings disclosed that variations in the instability of the genome produces new antigens, which affects the immune phenotype and immunotherapy response [14]. Long non-coding RNAs (lncRNAs) are considered to be incapable to encode proteins, and they play an indispensable regulatory role in tumors.…”
Section: Introductionmentioning
confidence: 99%
“… 171 , 172 Neoantigens are mostly caused by errors in the DNA replication process of cancer cells, and some are caused by environmental factors such as viruses, radiation, and chemicals. 173 Although personalized tumor vaccines are still in the exploratory stage, the currently reported clinical trials of individualized neoantigen vaccines have shown encouraging results, especially in the treatment of melanoma, with high accuracy and low side effects. 174 , 175 , 176 , 177 , 178 , 179 , 180 …”
Section: Main Textmentioning
confidence: 99%